Perspective of young adult male non-ballet dancers on ballet as a recreational activity for adolescent males - Lajo, Arianna Sophia L.
Participating in dance, such as ballet, as a recreational activity can be recommended to adolescents because it provides physical, mental, emotional, and psychosocial benefits. However, given that ballet is feminine and female-dominated, there are negative attitudes and prejudices towards males engaging in ballet. Thus, through qualitative descriptive research, this study aimed to describe and analyze the perspectives of young adult male non-ballet dancers from a state university in Metro Manila, Philippines on ballet as a recreational activity for adolescent males. A sample of 6 young adult male participants, 3 with short term ballet experience and 3 with no experience in ballet at all, were individually interviewed in-person. The interviews were expounded on and analyzed through reflexive thematic analysis and in consideration of the Theory of Planned Behavior. The common themes and concepts derived from the interviews were applied to a conceptual framework. The findings suggest that the participants, as well as male adolescents in general, were discouraged to participate because of (1) negative attitudes associated with difficulty, social elitism, and femininity, (2) disapproval of society, culture, and significant people, and (3) lack of capabilities or resources to participate. Participation can be encouraged through strategies that counter these negative factors. The findings can thus be applied in institutions planning to offer dance classes. Future similar studies are recommended to interview adolescent males, focus on participation during young adulthood, investigate change in perspectives, compare of female and male views, or explore perspectives on professional ballet participation.